Salzmann nodular degeneration features in a case of Kabuki make-up syndrome - Martins, Amélia (BMJ Case Rep, 2019)
Kabuki syndrome (KS) is a multiple congenital anomaly syndrome with diversified ophthalmological manifestations. We report a case of a boy with bilateral features of Salzmann nodular degeneration (SND) associated with KS. An 18-year-old Caucasian man with KS presented for a second opinion regarding incapacitating photophobia in his right eye, refractory to medical therapy. Biomicroscopy revealed bilateral subepithelial nodules in the midperiphery of the cornea, less extensive in the left eye, consistent with SND. Symptomatic improvement was achieved after superficial keratectomy, manually performed with a blade and adjuvant application of mitomycin C. We report a rare case of a KS patient with SND. Since KS manifestations may vary widely, it is important to perform an early ophthalmological examination for prompt detection and treatment of ocular abnormalities and thus improve life quality in these patients.